Assessing intraspecific variability and diversity in African yam bean landraces using agronomic traits - Olomitutu, O.E.; Abe, A.; Oyatomi, Olaniyi; Paliwal, R.; Abberton, Michael T. (MDPI, 2022)
Landraces are repositories for potential beneficial traits which could be used to develop varieties with enhanced qualities. Optimal utilization of the available large collection of landraces of African yam bean (AYB) presently conserved at the Genetic Resource Center, International Institute of Tropical Agriculture, Ibadan (GRC-IITA), requires an assessment of the magnitude and nature of genetic diversity within the germplasm. One hundred and ninety-six AYB accessions were evaluated during the 2018 and 2019 cropping seasons in three agro-ecologies of Nigeria, using a 14 × 14 triple lattice design. The accessions were assessed for fourteen agronomic traits. Accession, environment, and accession × environment interaction effects were significant (p < 0.05) for all the traits. Variances due to environment and accession × environment interaction were higher than the genotypic variances. Similarly, estimates of phenotypic coefficient of variation (PCV) were higher than genotypic coefficient of variation (GCV) for all traits. Broad-sense heritability ranged from 17.1% (days to maturity) to 66.4% (seed length). Seed yield per plant had positive significant genotypic correlation with all the studied traits, except pod length and seed length. The first three principal components accounted for 59.7% of the total variation among the accessions and comprised of the 14 traits. Five major clusters were delineated based on phenotypic characteristics. Genetic variation was present among the AYB accessions, and these results will be useful for setting breeding goals and conservation approaches.